2020
DOI: 10.21203/rs.3.rs-91574/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anxiety and Depression During COVID-19 Pandemic Among Medical Students in Nepal

Abstract: Background: Medical students’ psychological response to societal lockdown during the covid-19 pandemic has not been studied much. Our aim was to assess levels of anxiety and depression among medical students during the initial stages of the pandemic in Nepal and relate their distress to psychosocial and other relevant situational variables.Materials and Methods: A cross-sectional study with an online questionnaire was conducted among medical students at different colleges in Nepal. Hospital Anxiety and Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
1
17
0
4
Order By: Relevance
“…The study findings revealed that the prevalence of mild to severe depressive symptoms was high in medical students, and factors such as gender, struggling to get away from social media, and having sleep disturbances in the preceding 4 weeks were significantly associated with depressive symptoms. In our study, 80.2% of medical students had mild to severe levels of depressive symptoms, which was comparable to findings from Bangladesh (49.1%), India (74.6%) and Brazil (64.41%) but higher than those reported from Nepal (5.5%) and Iran (25.6%) (3,3,5,10,19,20). The disparity in prevalence could be due to the usage of multiple measurement scales and countries contexts.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The study findings revealed that the prevalence of mild to severe depressive symptoms was high in medical students, and factors such as gender, struggling to get away from social media, and having sleep disturbances in the preceding 4 weeks were significantly associated with depressive symptoms. In our study, 80.2% of medical students had mild to severe levels of depressive symptoms, which was comparable to findings from Bangladesh (49.1%), India (74.6%) and Brazil (64.41%) but higher than those reported from Nepal (5.5%) and Iran (25.6%) (3,3,5,10,19,20). The disparity in prevalence could be due to the usage of multiple measurement scales and countries contexts.…”
Section: Discussionsupporting
confidence: 81%
“…The global summation of the nine issues delineated the level of the severity of depression. Recommended cut off PHQ-9 scores for level of depression severity (12): minimal (score 0-4), mild (score 5-9), moderate (score 10-14), moderately severe (score [15][16][17][18][19], severe (score [20][21][22][23][24][25][26][27]. Patient Health Questionnaires had good internal consistency (Cronbach's Alpha = 0.77), adequate split-half reliability (r = 0.80) in our data.…”
Section: Depressive Symptoms Measurementioning
confidence: 60%
“…Students who may themselves have been affected with COVID-19 or those who are struggling with anxiety or depression may not volunteer due to health reasons as opposed to making the decision based on their beliefs. In a study assessing anxiety and depression levels among medical students in Nepal, several were found to be suffering from these mental health issues during the COVID-19 shutdown [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study also highlighted that students who were confined at home have undergone mental and emotional distress as there is lack of daily routine and physical activity, and limited social interaction to engage them productively, which may have resulted in a feeling of worthlessness, boredom and agitation 4 5. Adolescents, particularly university students, have been struck hard, as the pandemic has imposed a negative influence on their academic-related activities and professional development 6.…”
Section: Introductionmentioning
confidence: 99%